ANALYZING THE IMPACT OF INDIVIDUAL, GROUP, ORGANIZATIONAL, AND TECHNOLOGICAL FACTORS ON KNOWLEDGE SHARING ACTIVITIES AMONGST ACADEMICS IN INDONESIA - Lina Anatan; Wilson Bangun; Fransiscus Marcel (MIX: JURNAL ILMIAH MANAJEMEN, 2021)
Knowledge is the most important strategic resource for knowledge-based organizations such as higher education to achieve sustainable competitive advantage. Facing dynamic and unpredictable competition, organizations not only rely solely on a workforce training system that focuses on selecting workers who have specific knowledge, skills, abilities, or competencies, but also organizations must start thinking about how the knowledge sharing process can be carried out in organization. This study is conducted to investigate factors influencing knowledge sharing activities among academics in Indonesia. These factors include individual factors, group factors, organizational factors, and technological factors. This study involved academics from public and private universities in Indonesia and data collected through surveys. This study involved 141 respondents from 17 study programs which include 31 public and private universities in Indonesia. The results showed that individual factors, organizational factors, and technological factors had a significant influence on knowledge sharing activities among academics in higher education, while group factors did not have a significant effect on knowledge sharing activities between academics in universities in Indonesia